Personal Reflections on Tlingit Matriculture: Transcript - Ramos, Judith (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2026)
In this recorded interview, Judith Ramos shares her personal reflections about being a Tlingit woman and Tlingit matriculture. Transcript available (see PDF).LINK TO VIDEO INTERVIEW: Personal Reflections on Tlingit Matriculture